PENGGUNAAN SLOW DEEP BREATHING DALAM PENGONTROLAN TEKANAN DARAH PADA PENDERITA HIPERTENSI: STUDI LITERATURE REVIEW - Susanto, Tantut; Permatasari, Andina Yulia Dwi; Rasni, Hanny; Fauziah, Wahyuni (Kelimutu Nursing Journal, 2024)
Introduction: Uncontrolled blood pressure could affect health problems such as hypertension. Factors that cause hypertension are family medical history, sedentary lifestyle based on food consumption contains high fat, and also smoking behavior. Hypertension could be treated by alternative therapy such as slow deep breathing. Family roles as a support system are needed to guide the family member with hypertension to practice and implement slow deep breathing. Objective: This study aims to identify slow deep breathing intervention in controlling blood pressure based on research articles and family involvement in guiding slow deep breathing intervention to family members with hypertension. Method: The design of this study is using a literature review of articles using the search engine database of Proquest, Google Scholar, SpringerLink, ScienceDirect, PubMed, and PRISMA flowchart. Results: The results are showed from this study are that five articles met both the criteria of inclusion and exclusion. After being given by slow deep breathing intervention, hypertension patients are shown that the frequencies of oxygen that transmitted into organs through the blood vessels in releasing the baroreflex responds, which provides a relaxing effect and decreases the level of blood viscosity inside the blood vessels. Conclusion: This study could conclude that using slow deep breathing therapy could positively impact patients with hypertension and use family approach as primary support to improve health.